استخدام أسلوب تحليل الحساسية لتقييم الربحية التجارية لمشروع " التفريغ الصناعي" الممول في إطار الوكالة الوطنية لدعم تشغيل الشباب سوق أهراس (El-Wahat Journal for Research and Studies, 2017)
This Study Aims To Propose The Application Of Sensitivity Analysis Method As A Supporting Tool To The National Agency For Support Youth Employment In Its Assessment Of The Profitability Of The Investment Projects Submitted To It For The Purpose Of Financing. The Agency Bases Its Assessment Of These Projects Profitability Only On The Net Present Criterion Which   Could Lead To Misleading Results, Since It Does Not Take Into Account The Risk Of Changing Environment In Which These Projects Operate. The Use Of Sensitivity Analysis To Evaluate The Artificial Hatchery Project Profitability, In Order To Include The Element Of Risk And Uncertainty Element, Showed That The Project Profitability Is Sensitive To Any Implementation Delay And Changes In The Cash Flows Factor, If Cash Flows Declined By More Than 50% The Project Will Not Be Feasible, Which Is Confirmed By Sensitivity Indicator. However, Sensitivity Analysis Showed That The NPV Criterion Is Less Sensitive To Changes In The Discount Rate And The Cost Of Investment. Key Words-  Investment Project, Evaluation Of Profitability, The National Agency, Risk, Sensitivity Analysis.